Mengapa Kompetensi dan Karakteristik Wirausaha Penting? - Shahila Nurini Alizar; Eka Mariyanti (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
The objective of this study is to ascertain the impact of entrepreneurial characteristics and human resource competencies on the performance of MSMEs in Padang City. A total of 134 respondents were selected for inclusion in this study using the purposive sampling technique. This method allows for the selection of respondents based on specific criteria that are relevant to the research objectives. The findings indicate that entrepreneurial characteristics and human resource competencies positively and statistically significantly impact the performance of MSMEs in Padang City. Of the two independent variables subjected to analysis, human resource competencies were found to exert the most dominant influence on the performance of MSMEs, with a β value of 0.595. This suggests that the more proficient the competencies possessed by MSMEs, the superior the resulting performance. Further analysis indicates that enhancing human resource competencies, including technical knowledge, managerial abilities, and interpersonal skills, can directly enhance MSMEs’ operational effectiveness and competitiveness. MSMEs must implement continuous training and development programs to improve employees' technical, managerial, and interpersonal capabilities. Additionally, businesses must adopt cutting-edge technologies and business practices to improve operational efficiency. MSMEs should also collaborate more closely with local education and training institutions to gain easier access to relevant competency improvement programs.